Performance of a drip irrigation system using photovoltaic energy (Research, Society and Development, 2022)
The objective of the work was the use of a water pumping system for drip irrigation. The system was installed in the CASA (Alternative Systems Analysis Center) project. The energy used for the pumping was obtained by means of a Greatwatt horizontal axis photovoltaic panel installed on a self-supporting tower and a Shurflo 8000 model water pump. The trials were performed on days of open skies, cloudy and with few clouds, at different times and duplicated at each time. The energy produced was collected directly on site and the irrigation capacity was obtained by collecting the water and its uniformity estimated using the Christiansen Uniformity Coefficient (CUC) and the Distribution Uniformity Coefficient (CUD). The performance of the system varied according to the characteristics of the tests. The open-air days presented the highest values in relation to the energy produced, with an average of up to 15.1 Wh. On the other hand, the CUC and CUD values were within the acceptable range, most of them being considered excellent or higher than 90%. In this way, it can be verified the feasibility of using a solar photovoltaic system to obtain energy for irrigation in small properties in Cascavel-PR.